Types and Attributes of Writing Errors with Reference to Paragraph Writing - Juma, Al-Mahdi; Marai, Wraida; said, Hajer (مجلة كلية الاداب, 2022)
Errors are a fundamental part of language acquisition. Researchers have examined the learners’ errors to understand the process of second language acquisition. Findings suggest that understanding the sources errors can contribute to better second language teaching practices. The aim of this study paper is therefore to give a brief account of the types, techniques and treatment of second language learners' errors, with reference to paragraph writing. The data for this study were seventeen students at the under graduate level – University of Benghazi. The data for this study was collected via assignment given to the students in which they were asked to write a paragraph describing a family member. The results show that students at the department of English encounter serious problems related to paragraph writing; the total number of errors that Libyan students made were 97 error. The maximum number of errors were made in spelling was 44 which came to 45.3% of errors. On the other hand, the minimum number of errors in writing recorded in this study was in the wrong use of ‘capitalization’. The total number of errors in the use of capitalization was 1, which constituted 1.0 % of errors.